A conceptual framework of patient‐reported outcomes in people with venous leg ulcers. Issue 3 (14th December 2019) - Ruseckaite, Rasa; Richards, Catelyn; Rutherford, Claudia; Team, Victoria; Turnour, Louise; Franks, Peter; Weller, Carolina
Abstract: Venous leg ulcers (VLUs) are a common chronic often undertreated condition, which affects individual's health‐related quality of life (HRQoL). Numerous patient‐reported outcome measures (PROMs) have been validated to capture HRQoL in patients with VLUs. However, available instruments contain many items, are hard to use in clinical practice, and present with weak responsiveness. This study aims to determine clinical utility of an existing VLU‐QoL instrument and to develop a comprehensive PROs assessment framework to guide clinical practice treatment in people with VLUs in Australia. Semi‐structured qualitative interviews were conducted with VLU patients ( N = 13) and their managing clinicians ( N = 6) in Victoria, Australia. Interview topics covered content and face validity, appropriateness, and acceptability of the VLU‐QoL instrument to determine suitable and appropriate for use in clinical practice. Clinicians and patients agreed that a VLU‐QoL instrument was needed in clinical practice. Both clinicians and patients agreed it would be appropriate to answer PROMs questions prior to consultation with clinicians every 3–6 months. However, patients considered that some of the questions are ambiguous and too technical. Patients reported that it would be useful to include additional items relating to daily wound care, compression bandaging, and dressings. Clinicians reported that the VLU‐QoL instrument was too long and required restructuring to facilitate utility in practice. A conceptual framework for HRQoL in VLUs included traditional HRQoL components and VLU‐specific issues. Overall, the VLU‐QoL was well accepted, although changes to make it more concise, comprehensive, and to clearly reflect consumers' perspectives were lacking. The proposed conceptual framework will inform the development of a new PROM for use by clinicians and patients in clinical settings.